(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aims to assess the impact of marketing mix strategies on customer satisfaction of Self-Help Group (SHG) products, specifically home-based products and jute bags in Telangana state. The research utilizes multiple regression, correlation, and chi-square analyses to examine the relationship between various marketing mix elements and customer satisfaction. The study adopts a quantitative research approach, collecting data from a sample from self-help groups who are engaged with SHG products. The research variables include the marketing mix elements (product, price, promotion, and place) as independent variables, and customer satisfaction as the dependent variable. Multiple regression analysis is employed to explore the effects of the marketing mix elements on customer satisfaction. Correlation analysis is utilized to examine the strength and direction of relationships between the variables. Furthermore, chi-square analysis is conducted to investigate the association between demographic variables and customer satisfaction. The data was gathered from 268 respondents. The findings of this study contribute to the understanding of how marketing mix strategies influence customer satisfaction in the context of SHG products. The results reveal significant relationships between the marketing mix elements and customer satisfaction. The implications of this study suggest that SHGs should focus on continuously improving product quality, implementing competitive pricing strategies, enhancing promotional efforts, and ensuring convenient accessibility to maximize customer satisfaction. Finally, this research provides valuable insights for SHGs and other stakeholders involved in marketing SHG products, enabling them to make informed decisions regarding marketing mix strategies to enhance customer satisfaction and drive sustainable growth in Telangana state.